Trends in H2S-Donors Chemistry and Their Effects in Cardiovascular Diseases - Angela Corvino; Francesco Frecentese; Elisa Magli; Elisa Perissutti; Vincenzo Santagada; Antonia Scognamiglio; Giuseppe Caliendo; Ferdinando Fiorino; Beatrice Severino (MDPI AG, 2021)
Hydrogen sulfide (H2S) is an endogenous gasotransmitter recently emerged as an important regulatory mediator of numerous human cell functions in health and in disease. In fact, much evidence has suggested that hydrogen sulfide plays a significant role in many physio-pathological processes, such as inflammation, oxidation, neurophysiology, ion channels regulation, cardiovascular protection, endocrine regulation, and tumor progression. Considering the plethora of physiological effects of this gasotransmitter, the protective role of H2S donors in different disease models has been extensively studied. Based on the growing interest in H2S-releasing compounds and their importance as tools for biological and pharmacological studies, this review is an exploration of currently available H2S donors, classifying them by the H2S-releasing-triggered mechanism and highlighting those potentially useful as promising drugs in the treatment of cardiovascular diseases.